How can a new UN ocean treaty change the course of capacity building?. Issue 5 (1st March 2022) - Harden‐Davies, Harriet; Amon, Diva J.; Chung, Tyler‐Rae; Gobin, Judith; Hanich, Quentin; Hassanali, Kahlil; Jaspars, Marcel; Pouponneau, Angelique; Soapi, Katy; Talma, Sheena; Vierros, Marjo
Abstract: Few States are able to undertake scientific research in the half of the planet that lies in marine areas beyond national jurisdiction. Capacity building is therefore a key part of the development of a new international legally binding instrument for the conservation and sustainable use of marine biological diversity of areas beyond national jurisdiction, under the United Nations Convention on the Law of the Sea (BBNJ Agreement). The final negotiations for the BBNJ Agreement are scheduled for early 2022, after almost two decades of development. There is an urgent need to address remaining questions relating to capacity building to secure an effective and equitable outcome from this process and safeguard the global ocean commons. Persisting gaps in scientific capacity cast doubt on the adequacy of past and current approaches to implement long‐standing international commitments. There is a need to build equitable partnerships for long‐term outcomes. As an international legally binding instrument, the BBNJ Agreement is a critical opportunity to change the course of capacity building by strengthening the international legal framework, including funding, information‐sharing, monitoring and decision‐making. This rapidly closing window to develop international legal obligations, collaboration frameworks and funding mechanisms is relevant not only to the conservation of the global ocean commons, but also for ocean sustainability more generally as the UN Ocean Decade begins.